О происхождении христианской архитектуры ранневизантийского Херсонеса - Завадская, И.А. (Материалы по археологии, истории и этнографии Таврии, 2001)
Наиболее яркими и характерными для ранневизантийского периода памятниками христианской архитектуры Херсонеса являются трехнефные базилики, превратившиеся на протяжении длительного функционирования в центры целых храмовых комплексов. В настоящее время на территории городища известны остатки одиннадцати таких базилик. Comparing architectural forms of local churches and their Byzantine analogues the author demonstrates the leading role of the capital city school in forming early medieval monuments of church architecture in Chersonesos. The Hellenistic type of all Chersonesos basilicas, as well as the decorations of their interior, building technology, liturgical arrangement confirm it. Architectural orientation to Constantinople is in the agreement with the fact of direct dependency of Chersonesos diocese on Constantinople patriarch, which was secured by Khalkidon Council in 451. Besides capital city features Chersonesos architecture absorbed the elements of other regional schools (Syrian, Asian Minor, Trans-Caucasian).